2016
DOI: 10.1103/physrevb.93.184108
|View full text |Cite
|
Sign up to set email alerts
|

First-principles investigation of hydrogen interaction with TiC precipitates inα-Fe

Abstract: A correct description of hydrogen diffusion and trapping is the prerequisite for an understanding of the phenomenon of hydrogen embrittlement. In this study, we carried out extensive first-principles calculations based on density functional theory to investigate the interaction of H with TiC precipitates that are assumed to be efficient trapping agents mitigating HE in advanced high-strength steels. We found that there exists a large variety of possible trapping sites for H associated with different types of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
64
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 143 publications
(71 citation statements)
references
References 75 publications
6
64
0
1
Order By: Relevance
“…This was later confirmed by first-principles calculations [10], which further demonstrated that H accumulation can weaken the interface, resulting in hydrogen-enhanced decohesion and subsequent fracture formation.…”
Section: Introductionsupporting
confidence: 51%
See 2 more Smart Citations
“…This was later confirmed by first-principles calculations [10], which further demonstrated that H accumulation can weaken the interface, resulting in hydrogen-enhanced decohesion and subsequent fracture formation.…”
Section: Introductionsupporting
confidence: 51%
“…Another possible scenario can be the formation of percolating networks of C vacancies which act as energetically favored pathways for hydrogen to diffuse from the interface to the bulk of the carbide, as observed for TiC [10]. We can further define the hydrogen-vacancy complex formation energy as the sum of the C vacancy formation energy and the H trapping energy within this vacancy.…”
Section: Stacking Sequence Of Layers In Scmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, there is the largest hydrogen dissolution energy at the hollow site, showing the strongest solution effect of hydrogen locally . Other than the dissolution energy in the top site of S–Fe, the dissolution energies of hydrogen at other sites are above 1 eV, which is greater than the dissolution energy of hydrogen in semi‐coherent α ‐Fe/TiC interfaces (0.32–0.5 eV) by Stefano et al, and that of hydrogen at oriented grain boundaries of α ‐Fe (0.1–0.5 eV) by Mirzaev et al Thus, the dissolution (or trapping) of hydrogen at MnS inclusions is more stable than other sites such as lattice. As a result, the H atoms tend to be irreversibly trapped at numerous small inclusions with limited amount at each site, limiting the hydrogen pressure that can be developed locally and improving the resistance of the steel to HIC.…”
Section: Discussionmentioning
confidence: 91%
“…In particular, in low carbon steels, such as high-strength low-alloy (HSLA) steels, homogeneously distributed nano-sized MX precipitates significantly increase the yield stress. In order to exploit the benefits of the MX precipitates in steels, i.e., precipitation strengthening, grain refinement, and enhancing resistance to hydrogen embrittlement by trapping hydrogen [1][2][3], etc., a detailed characterization of the structures and energetics of the phase interfaces is required. For example, prevention of precipitate coarsening by Ostwald ripening during subsequent processing is crucial to realizing a sufficient precipitation hardening effect in the final product.…”
Section: Introductionmentioning
confidence: 99%